Knowledge about COVID-19 and Practices among Hemodialysis Technicians in the COVID-19 Pandemic Era - Amit S. Pasari; Amol Bhawane; Manish R. Balwani; Priyanka Tolani; Vishal Ramteke; Nishant Deshpande (International Journal of Nephrology)
Introduction. Hemodialysis technicians play a crucial role in infection control practices in hemodialysis units. Thus, it is important to assess the knowledge and attitude towards COVID-19 among hemodialysis technicians in this pandemic situation. Materials and Methods. An online survey composed of 22 closed-ended questions using Google Forms was conducted in the month of April (13th to 19th) 2020. The survey consisted of questions regarding the knowledge of COVID-19 and current hemodialysis practice among hemodialysis technicians. The study was approved by the institutional ethics board. The survey was administered online through a mobile phone invitation. Basic statistics (mean and standard deviation or total number and percent) were computed for all covariates. Results. Out of 150, 115 technicians participated in the survey. 80.9% of the participants were males. The mean age of respondents was 28.22 + 6.97 years. Most of the respondents could correctly identify fever (87.8%), breathlessness (86.08%), and dry cough (81.7%) as the symptoms of COVID-19 infection. 75.7% of the technicians were aware that it can be transmitted by asymptomatic persons. 61.1% of the technicians were segregating patients who had symptoms such as fever and cough to the last shift of the day. 81.1% of the technicians read the guidelines issued by the Indian Society of Nephrology—COVID-19 working group. But, only 25.5% of the respondents could rightly identify to keep a minimum distance of two meters between two beds while dialyzing a suspected patient of COVID-19 along with other patients to minimise risk of COVID-19 transmission. 60% of the technicians have received hydroxychloroquine as prophylaxis against coronavirus infection. Conclusion. Our study shows a significant knowledge gap among hemodialysis technicians about COVID-19. Effective COVID-19 education campaigns should be carried out intensively with relevant information among hemodialysis technicians to address the knowledge gap. A well-informed hemodialysis technician can prove to be a great tool to spread the right infection control practices among dialysis-dependent patients.